Voluntary Simplicity dan Sustainable Clothing Purchase Intention dengan Environment Concern sebagai Variabel Mediasi - Friska; Robert Kristaung (PT. Cendekia Sapta Indonesia, 2023)
This research aims to analyze the effect of voluntary simplicity on purchase intention mediated by environmental concern . The research conducted was descriptive quantitative research by distributing questionnaires. This study uses the hypothesis testing method. Hypothesis testing uses the Structural Equation Model (SEM) with AMOS 25 software. The data in this study were collected from 200 respondents in DKI Jakarta. With the withdrawal method using Purposive Sampling. The results of hypothesis testing in this study show that there is an influence of voluntary simplicity on purchase intention and environmental concern mediate the effect between voluntary simplicity and purchase intention. From the results of this study it is hoped that it can provide input for company managers so that they can pay attention to the factors that might help to increase the selling. Keywords: Voluntary Simplicity, Environmental Concern, Purchase Intention